Peripherally Acting Opioids in Orofacial Pain - Liu, Qing; He, Hongwen; Mai, Lijia; Yang, Shengyan; Fan, Wenguo; Huang, Fang (Frontiers in Neuroscience, 2021)
Activation of opioid receptors by exogenous or endogenous opioids can produce a significant analgesic effect in peripheral tissues. Numerous researchers have demonstrated the expression of peripheral opioid receptors (PORs) and endogenous opioid peptides (EOPs) in the orofacial region. Growing evidence has shown the involvement of PORs and immune cell-derived EOPs in the modulation of orofacial pain. In this review, we discuss the role of PORs and EOPs in orofacial pain and the possible cellular mechanisms. Furthermore, the potential development of therapeutic strategies for orofacial pain is also summarized.